Phytochemical Investigation And Assessment Of Anti-Hyperlipidemic Potential Of Dianthus Chinenis Plant Extract On Wistar Rats - Priya, Shakshi; Dhakad, Kehar Singh; Kumar Singhai, Akhilesh (Journal of Neonatal Surgery, 2025)
The study aimed to explore the phytochemical profile and assess the anti-hyperlipidemic potential of Dianthus chinensis plant extract on Wistar rats. The methanol extract of Dianthus chinensis was subjected to qualitative and quantitative analyses to identify its phytoconstituents, including phenolic compounds, flavonoids, alkaloids, and saponins. The total phenolic content (TPC) and total flavonoid content (TFC) were estimated, and their antioxidant potential was evaluated through the DPPH assay. In vivo studies on Wistar rats induced with hyperlipidemia using a high-fat diet demonstrated a significant reduction in serum lipid profiles, including total cholesterol, triglycerides, low-density lipoprotein, and very low- density lipoprotein, along with an increase in high-density lipoprotein levels. The methanol extract exhibited comparable effects to the standard drug, lovastatin, suggesting its potential as an effective natural agent for managing hyperlipidemia. Furthermore, serum biochemical tests revealed the hepatoprotective properties of Dianthus chinensis extract. The findings highlight its therapeutic potential in managing hyperlipidemia and promoting liver health